Antimicrobial Resistance on Escherichia coli from Poultry Production on Blitar, Indonesia - Freshinta Jellia Wibisono1 , Bambang Sumiarto2 , Tri Untari3 , Mustofa Helmi Effendi4,5, Dian Ayu Pe (Indian Journal of Forensic Medicine & Toxicology, 2020)
The use of antibiotics in poultry can encourage antibiotic resistance, one of which is Escherichia coli whichproduces Extended Spectrum Beta-Lactamase. Extended Spectrum Beta-Lactamase is most produced byEscherichia coli. This study was carried out in a cross sectional descriptive manner aimed to determinethe prevalence of ESBL in Escherichia coli bacteria in layer and broiler chicken farms in Talun andKademangan subdistricts, Blitar district. Samples of 76 cloacal swabs were taken from laying hens andbroilers. Positive isolates of Escherichia coli were tested for antibiotic sensitivity on agar-resistant MuellerHinton agar and Escherichia coli-resistant beta lactam (ampicillin) groups and then confirmed using theDouble Disc Synergy Test, to confirm as Escherichia coli producing ESBL. The results showed a highprevalence of MDR in commercial chicken farms in Blitar district. Escherichia coli has MDR resistanceproperties in Layer Chicken in Talun sub-district by 88.23%, and in Kademangan sub-district by 63.16%,while for Broiler chickens in Talun sub-district by 90% and in Kademangan sub-district by 100%. Theprevalence of Escherichia coli producing ESBL in Kademangan Sub-district was 15.79% and in Talun subdistrict by 5.88%, while in Broiler chickens in Kademangan sub-district was 85%, and in Talun sub-districtthe Escherichia coli producing ESBL was not detected.